2005
DOI: 10.1128/mcb.25.3.888-895.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Transcription-Replication Collisions in Bacteria

Abstract: While collisions between replication and transcription in bacteria are deemed inevitable, the fine details of the interplay between the two machineries are poorly understood. In this study, we evaluate the effects of transcription on the replication fork progression in vivo, by using electrophoresis analysis of replication intermediates. Studying Escherichia coli plasmids, which carry constitutive or inducible promoters in different orientations relative to the replication origin, we show that the mutual orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
156
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 49 publications
15
156
1
Order By: Relevance
“…This is consistent with the report that the bacteriophage T4 replication machinery paused transiently in head-on collisions with a transcription complex, although pausing was not observed when the collision was co-directional (26). Head-on collisions of the E. coli DNA replication and transcription machineries have been reported to reduce replication fork movement in vivo (27,28). All seven rRNA operons in the E. coli genome are oriented such that transcription and replication occur in the same direction, presumably to facilitate disassembly of transcription complexes during replication.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the report that the bacteriophage T4 replication machinery paused transiently in head-on collisions with a transcription complex, although pausing was not observed when the collision was co-directional (26). Head-on collisions of the E. coli DNA replication and transcription machineries have been reported to reduce replication fork movement in vivo (27,28). All seven rRNA operons in the E. coli genome are oriented such that transcription and replication occur in the same direction, presumably to facilitate disassembly of transcription complexes during replication.…”
Section: Discussionsupporting
confidence: 91%
“…This effect has been attributed to an enhanced replication block when the transcription machinery is directed toward an oncoming replication fork. Such transcription-dependent replication pause/stall sites have been observed in yeast [17,18] as well as in bacteria [19]. In addition, in E. coli, it has been observed that the manner in which a given DNA lesion is dealt with depends on the direction of replication [20].…”
Section: Introductionmentioning
confidence: 78%
“…Paused replication forks can lead to double-strand breaks (41,43,44) and there is evidence of increased mutagenesis in the local region of doublestrand breaks (45). Essential genes are greatly enriched among transcripts cooriented with replication (20,21), probably because cells are more sensitive to mutations in essential genes and it is important to avoid disruption of their replication by head-on transcription (11). Highly expressed genes are also enriched among the cooriented transcripts (7), probably because transcription from these genes would disrupt replication more frequently when oriented opposite to replication.…”
Section: Selective Pressures For Coorientation Of Transcription and Rmentioning
confidence: 99%
“…Plasmid DNA replication in E. coli can also be hindered by head-on transcription from a strong inducible promoter, probably because of collisions between the replisome and RNAP (ref. 11 and references therein). Head-on transcription of tRNA genes in eukaryotes can also cause pausing of replication (12).…”
mentioning
confidence: 99%